Meaning and moral order : explorations in cultural analysis - Wuthnow, Robert (Berkeley ; London : University of California Press, 1989)
Meaning and Moral Order goes beyond classical, neoclassical, and poststructural theories of culture in its attempt to move away from problems of meaning to a more objective concept of culture. Innovative, controversial, challenging, it will compel scholars to rethink many of the assumptions on which the study of ideology, ritual, religion, science, and culture have been based.
Frontmatter -- Contents -- Preface -- 1. Cultural Analysis -- 2. Beyond the Problem of Meaning -- 3. The Structure of Moral Codes -- 4. Ritual and Moral Order -- 5. Moral Order and Ideology -- 6. Social Selection Among Ideological Forms -- 7. The Moral Basis of Cultural Change -- 8. The Institutionalization of Science -- 9. State Structures and Cultural Reform -- 10. Conclusion -- Notes -- Bibliography -- Name Index -- Subject Index
Includes bibliographical references (pages 379-416) and index.
Print version record.
English.
JSTOR
Keywords: Culture; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE -- Sociology -- General; Culture; Cultuursociologie; Cultuur; Zingeving; Moraal